The impact of timing for initiating formula feeding on the short-term prognosis of very low birth weight infants - Katsumi Mizuno (Global Pediatrics)
Background: For very low birth weight (VLBW) infants, breast milk, particularly mothers' own milk (MOM), is the optimal nutrition. Donor human milk (DHM) is recommended when MOM is insufficient. However, the optimal timing for transitioning from DHM to formula remains unclear. This study examines the impact of formula initiation timing on complications in VLBW infants. Methods: We analyzed data from 744 VLBW infants (<1500 g) who initiated enteral feeding with DHM within 24 hours of birth using a human milk bank database (2018–2024). Postmenstrual age (PMA) at formula initiation was assessed for associations with bronchopulmonary dysplasia (BPD), home oxygen therapy (HOT), retinopathy of prematurity (ROP), and necrotizing enterocolitis (NEC). Results: The median PMA at formula initiation was 34.6 weeks. Delayed formula initiation reduced the risk of BPD, HOT, and NEC. Compared to formula initiation before 32 weeks, odds ratios for BPD ranged from 0.186 (34–36 weeks) to 0.239 (no formula). Formula initiation at 32–34 weeks significantly lowered ROP requiring treatment (OR 0.305). Logistic regression analysis indicated a trend toward reduced NEC risk when formula initiation occurred after 34 weeks (p = 0.0504). Conclusion: Delaying formula initiation until after 34 weeks PMA reduces complications in VLBW infants. Early enteral nutrition with MOM or DHM within 24 hours of birth is crucial, and later formula introduction may provide better outcomes. Further studies are needed to refine feeding guidelines